Numerical modeling of seismic responses from fractured reservoirs by the grid-characteristic method - Leviant, Vladimir; Kvasov, Igor; Petrov, Igor (Igor B.) (Geophysical developments series, 2019)
Using direct seismic responses of fractures and fracture zones to obtain location and characteristic information is a promising direction of investigation. This book addresses properties of fractured media seismic waves by describing, modeling, and analyzing responses from discrete fractured media, and proposes a methodology for direct detection.